Hidden - Michaels, Fern (Kensington Publishing Corp., 2021)
At first glance, few would guess that Luna and Cullan Bodman are siblings. Cullan, efficient and serious, is rarely out of a business suit. Luna reads palms and tarot cards, and loves flowing skirts and dangling jewelry that matches her unconventional spirit. Still, her artistic eye is an asset to the family's furniture restoration business. When Cullan stumbles across something unexpected in a piece he just acquired, and a client of Luna's reveals more than they should in a reading, the two put aside their differences to right a wrong. At stake is the future of a billion-dollar corporation, and as Luna and Cullan quickly discover, there are people who will stop at nothing to get what they believe they're owed.